Doğu’nun son kilise babası Yuhanna ed-dımaşkī (649-749) ve İslâm - Taşpınar, İsmail (Marmara Üniversitesi İlahiyat Fakültesi Dergisi, 2001)
Throughout the history, Christianity and Islam had mutual struggle in political and economic fields. The consequences of this struggle deeply effected relations of these two communities. One of this effect is the mutual misunderstandings in obtaining information about each others. This article deals with misinformations about Islam in the middle age. In focusing on John of Damascus’s (Yuhanna ed-Dımaşkī) –the last Father of the Eastern Church- famous work’s De Haeresibus, especially the 100. part which deals with Islam. The translation of the stated part attached to the text.